Antigenomic Hepatitis delta virus ribozymes self-cleave in 18 M formamide. - Smith, J B (1991)
The ribozymes derived from Hepatitis delta virus (HDV) RNA appear unique in their sequence requirements for self-cleavage. While truncating the 1679 nucleotide antigenomic HDV RNA, we have characterized the cleavage requirements of a number of ribozymes of intermediate length. Two of these, containing 186 and 106 HDV nucleotides respectively, cleaved to completion in the presence of 18 M formamide. The 186 nucleotide ribozyme also cleaved to completion in 10 M urea. Removal of an additional 10 nts from the 3' terminus of the 106 nt ribozyme resulted in a loss of the ability to cleave in high concentrations of the denaturants. The interaction of nucleotides near the cleavage site with a sequence within this 10 base region may confer unusual stability on these ribozymes.